2020
DOI: 10.3390/su12051866
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Effect between ESG and Green Innovation and Its Impact on Firm Value from the Perspective of Information Disclosure

Abstract: Few studies have been conducted on whether the coexistence of green innovation and corporate social responsibility (CSR) has a favorable interaction effect on firm value. This interaction effect is of great significance for enterprises balancing resource allocation between two factors in the future. Meanwhile, information disclosure can reflect the efforts of enterprises in taking on CSR. Therefore, taking China's listed companies as an example, this paper studies the interaction effect of CSR after being divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 43 publications
5
57
2
9
Order By: Relevance
“…This result is supported with Atan, Alam, Said, and Zamri (2018), Tarmuji, Maelah andTarmuji (2016), andMiralles-Quirós et al (2018) whereby it is found that social practices were negative. However, this result differs with Setyahuni and Handayani (2020), Zhang, Qin, and Liu (2020), Qiu, Shaukat and Tharyan (2016), Brogi and Lagasio (2019), Yoon, Lee and Byun et al (2018) and Qureshi, Kirkerud, Theresa, and Ahsan (2020) studies whereby it is found that social practices were positive and significant on firm value.…”
Section: Regression Analysis Between Social Practices and Firm Valuecontrasting
confidence: 98%
See 2 more Smart Citations
“…This result is supported with Atan, Alam, Said, and Zamri (2018), Tarmuji, Maelah andTarmuji (2016), andMiralles-Quirós et al (2018) whereby it is found that social practices were negative. However, this result differs with Setyahuni and Handayani (2020), Zhang, Qin, and Liu (2020), Qiu, Shaukat and Tharyan (2016), Brogi and Lagasio (2019), Yoon, Lee and Byun et al (2018) and Qureshi, Kirkerud, Theresa, and Ahsan (2020) studies whereby it is found that social practices were positive and significant on firm value.…”
Section: Regression Analysis Between Social Practices and Firm Valuecontrasting
confidence: 98%
“…This result is supported with Setyahuni and Handayani (2020); Qureshi, Kirkerud, Theresa and Ahsan (2020); Irawan et al (2021); Brogi and Lagasio (2019); Yoon, Lee, and Byun et al (2018), Atan et al (2018), andMiralles-Quirós et al (2018) studies whereby it is found that environmental practices were positive and significant on firm value. However, this result also differs with Tarmuji, Maelah, and Tarmuji, (2016); Zhang, Qin, and Liu (2020); Qiu, Shaukat, and Tharyan (2016) studies whereby it is found that environmental practices are not significant on firm value.…”
Section: Regression Analysis Between Environmental Practices and Firm Valuecontrasting
confidence: 91%
See 1 more Smart Citation
“…Control variables. Guided by Garcia et al (2017), Landi and Sciarelli (2019), Miralles-Quirós et al (2019), Paltrinieri et al (2020), Sun et al (2019) and Zhang et al (2020), ROA, firm size (SIZE), debt ratio (LEV) and firm age (AGE) are chosen as control variables. In addition, industry dummy (INDUSTRY), region dummy (REGION) and year dummy (YEAR) is also introduced in the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between CSR and firm performance is mixed in academics. Most studies (Buallay, 2019; Chelawat and Trivedi, 2016; Cho and Lee, 2019; Di Tommaso and Thornton, 2020; Filbeck et al , 2019; Jackson and Hua, 2009; McGuire et al , 1988; Miroshnychenko et al , 2017; Orlitzky et al , 2003; Rodríguez-Fernández et al , 2019; Schuler and Cording, 2006; Weber, 2014; Yoon et al , 2018; Zhang et al , 2020; Zhao et al , 2018) found superior financial performance from CSR-related investments. For example, Chelawat and Trivedi (2016) confirmed that good corporate ESG generates enhanced financial performance for companies in the context of India.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%